Penerapan Sistem Pendukung Keputusan dalam Penentuan Alat Bantu Media Pembelajaran Fisika Terbaik Menggunakan Metode PSI - Dwina Pri Indini; Mesran Mesran; Agung Triayudi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Technology in the Revolutionary Era 4.0 and Society 5.0 made changes in the manual learning system to digital. Along with the development of technology that makes technology and humans very difficult to separate. There are many ways to acquire learning knowledge, one of which is to use learning media tools that are already available on mobile phones. There are so many physics learning media tools available that make students confused in determining the best media to use. In determining physics learning media tools when learning online there are several criteria for Storage Capacity, Application Features, Number of Materials, Number of Language Choices, Number of Users and Rating Reviews. Based on these problems, a decision support system is needed as a problem solving technique and is assisted by a method that can produce an accurate final value. The method is the Preference Selection Index (PSI) method which is very helpful in generating the best weight and preference values ​​from alternative data and criteria so that the final result is that the best physics learning media tool is in Alternative F4 with a value of 0.79563, namely the PhyWiz application.